Salmonella sp. and Shigella sp.in House Flies in Jatinangor - Poravi, Reemarachna; Sadeli, Ramlan; Fitrasanti, Berlian Isnia; Sudigdoadi, Sunaryati (Althea Medical Journa, 2014)
Background: Diarrhea is a common problem in Indonesia and mostly caused by pathogenic bacteria such as Salmonella sp. and Shigella sp., transmitted by house flies. The incidence of acute diarrhea has been rising over the years. The aim of this study is to determine if Salmonella sp. and Shigella sp. can be found in house flies in Jatinangor.Methods: A descriptive study was done, involving 20 samples of house flies caught from houses and street vendors in Jatinangor during the period of March 2012 to January 2013. Bacteria were isolated from house flies and identified using various biochemical tests.Results: Shigella sp. was isolated from 5% of the house flies caught in Jatinangor. The house flies caught from the street vendors revealed a higher percentage of bacteria than those caught from houses.Conclusion: Only Shigella sp. can be isolated from house flies in Jatinangor. However, a small percentage of Shigella sp. was also found from the house flies captured around Jatinangor. [AMJ.2014;1(1):17â20]Keywords: house flies, Salmonella sp., Shigella sp.Salmonella sp. dan Shigella sp. pada Lalat Rumah di JatinangorLatar Belakang: Di Indonesia, diare merupakan masalah kesehatan yang sering terjadi dan sebagian besar disebabkan oleh bakteri pathogen seperti Salmonella sp. and Shigella sp yang terdapat pada lalat rumah. Angka kejadian diare akut terus meningkat dari tahun ke tahun. Tujuan dari penelitian ini adalah untuk menemukan bakteri Salmonella sp. dan Shigella sp. pada lalat rumah di Jatinangor.Metode: Penelitian ini merupakan penelitian deskriptif yang melibatkan 20 sampel lalat rumah yang ditangkap dari rumah dan pedagang kaki lima (PKL) di Jatinangor selama periode Maret 2012âJanuari 2013. Bakteri diisolasi dari lalat rumah dan diidentifikasi dengan menggunakan berbagai tes biokimia.Hasil: Shigella sp. diisolasi dari 5 % lalat rumah yang tertangkap di Jatinangor . Lalat rumah yang ditangkap dari PKL mempunyai persentase yang lebih tinggi daripada bakteri yang ditangkap dari rumah.Simpulan: Hanya Shigella sp. yang dapat diisolasi dari lalat rumah di Jatinangor. Sebagian kecil dari Shigella sp. juga ditemukan dari lalat rumah yang ditangkap di sekitar Jatinangor.Kata kunci: lalat rumah , Salmonella sp , Shigella sp